Lipolysis and Oxidation in Ultra‐High Temperature Milk Depend on Sampling Month, Storage Duration, and Temperature. Issue 5 (23rd April 2019) - Lu, Jing; Langton, Maud; Sampels, Sabine; Pickova, Jana
Abstract: During storage, some factors (for example, storage duration and temperature) can affect milk stability and consumer acceptability. Thiobarbituric acid reactive substances (TBARSs), lipid classes, and fatty acid profiles in stored ultra‐high temperature (UHT) milk were analyzed to assess the effects of storage time and temperature on lipid oxidation and lipolysis. With storage duration up to 12 months, the milk fat phase was separated and showed high levels of oxidation and lipolysis, manifested as increased levels of TBARS and free fatty acids. High oxidation levels decreased the percentage of unsaturated fatty acids (UFAs) in triacylglycerol and phospholipids. Higher storage temperatures (20, 30, and 37 °C) resulted in a higher degree of fat aggregation, oxidation, and lipolysis compared with refrigerated storage (4 °C). Additionally, sampling month of raw milk (May, July, and November) affected the lipid profiles of UHT milk during storage, with more UFA oxidized in July than in the other 2 months.